2019
DOI: 10.1108/qae-01-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Higher education service quality, student satisfaction and loyalty

Abstract: Purpose The purpose of this study is to validate the higher education service quality (HESQUAL) scale using a confirmatory approach and test an improved structural model that predicts student loyalty from image, perceived value, satisfaction and service quality. In addition to validating the HESQUAL scale using a confirmatory approach, two other main limitations in the extant literature are addressed. Design/methodology/approach The model is tested using data collected from 501 students enrolled in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 76 publications
(149 reference statements)
7
61
1
5
Order By: Relevance
“…Using a valid instrument and a conceptual model that fitted well with the data, the results of this research confirm the established relationship between satisfaction and loyalty, which considers satisfaction is the most influential predictor of loyalty (Oliver, 1980;Teeroovengadum et al, 2019). With regard to the impact of service quality, while acknowledging that parents may have different approaches to assessing educational service quality, we still hypothesized that core educational quality could positively influence parents' satisfaction and loyalty.…”
Section: Discussionsupporting
confidence: 66%
“…Using a valid instrument and a conceptual model that fitted well with the data, the results of this research confirm the established relationship between satisfaction and loyalty, which considers satisfaction is the most influential predictor of loyalty (Oliver, 1980;Teeroovengadum et al, 2019). With regard to the impact of service quality, while acknowledging that parents may have different approaches to assessing educational service quality, we still hypothesized that core educational quality could positively influence parents' satisfaction and loyalty.…”
Section: Discussionsupporting
confidence: 66%
“…The concept of quality, which can help organizations to gain competitive advantage and success in the market, has been applied in different service sectors. Service quality in higher education also was of the interest of many researchers by considering its two basic stakeholders: students and industry (Teeroovengadum, Nunkoo, Gronroos, Kamalanabhan, & Seebaluck, 2019). Furthermore, a study by Teeroovengadum, Kamalanabhan, and Seebaluck (2016) defines service quality in the higher education context as "the difference between what a student expects to receive and her/his perceptions of actual delivery."…”
Section: Service Qualitymentioning
confidence: 99%
“…ElAlfy and Abukari have highlighted that facilities, academic and administrative services are the main pillars of service quality in higher education sector [11]. Teeroovengadum et al have carried out an empirical study with students in Mauritius and found that technical service quality, perceived image, and value influence students' satisfaction [12]. Phuc et al have investigated master program in economic management to identify factors affecting outcome-based education.…”
Section: Related Workmentioning
confidence: 99%